AN ANALYSIS OF STUDENTS’ ESSAY AT ENGLISH DEPARTMENT OF UNIVERSITY PASIR PENGARAIAN - -, Eripuddin (Universitas Pasir Pengaraian, 2016)
This article discusses about the students’ problem in making an essay. The purpose of this article was to find out the students’ problem in making an essay.Object of this article was students’ essay that took by random sampling. The instrument used in this artcle were a test, interview and documentation. From the analysis it was found that the student was the difficulty to develop the ideas, lack of understanding in citing of experts’ opinion, and the lack of references. It can conclude that the basic problem of makin essay was the english department did not have a complete facilities to support the students’ skill.